Real Happiness at Work - Salzberg, Sharon (HighBridge, 2013)
How would you like to be calmer, less distracted, more productive, and more content at your job? You might think it would take more hours in the day, a better boss, more support, less interference, a shorter commute-and the list goes on. Most of the things we think would help are either not in our control or simply not realistic. But there is one thing we can do to achieve the qualities we seek, and it can be done invisibly and often: meditation. Meditation? Can you imagine meditating at work? Who has time for that? Real Happiness at Work will show why you don't have time not to do it. Sharon Salzberg has identified Eight Pillars of Happiness in the Workplace. They are: balance, concentration, resilience, integrity, meaning, connection, compassion, and open awareness. With short, subtle meditations to use pre- or post-meeting, in coping with unreasonable people, in finding meaning in seemingly meaningless tasks, and for dealing with mistakes, Real Happiness at Work will provide what we all seek-happiness-and what we all need-peace and productivity.